Pathophysiologic Perspectives on Muscle Tension Dysphonia - James P Dworkin-Valenti; Robert J Stachler; Noah Stern; Esmael H Amjad (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
It is difficult to quantify the incidence of hyperfunctional muscle tension dysphonia (H-MTD). Although voice disorders in general have been noted to affect approximately 10% of the population in the United States, up to 40% of patient visits to voice specialists are for symptoms of H-MTD. Clearly this condition is a very common vocal pathology, yet its differential diagnosis is not always straightforward. The primary purpose of this tutorial is to present a comprehensive literature review on this condition, with particular focus on alternative etiologic theories and differential diagnostic and treatment techniques. The secondary purpose of this tutorial is to increase awareness that this disorder is a complex condition with highly variable causes, features, and treatment requirements. As a consequence of recent advances in the field of neurolaryngology, and for completeness, the neurological substrates of voice and speech production are also discussed in this review. This information is included to evoke a theoretical onversation about possible patho-neurologic correlates in some patients with H-MTD; especially those who do not respond favorably to standard behavioral therapy strategies. Whereas only a brief discussion of treatment options is rendered in this paper, more detailed information on this topic will be covered in a forthcoming companion tutorial.